The Importance of Pop Culture and Media in Increasing Citizens’ Cyber Defense Capacity: The Case of Estonia - Kont, Kate-Riin (Information & Media, 2026)
While it is widely acknowledged that cyber risks can be managed and mitigated, they cannot be entirely eliminated. This reality underscores the importance of strengthening security awareness, fostering appropriate attitudes, and developing sound cyber hygiene from an early age. Such efforts not only reduce human error-related incidents but also help cultivate future cybersecurity professionals. Cultural approaches may provide a particularly effective means of intervention. Cultural activities – ranging from theater, film, television, music, and literature – can reach diverse audiences and shape behavioral norms in ways that purely technical or informational campaigns often cannot. Although pop culture frequently exaggerates or dramatizes cybersecurity, it simultaneously plays a significant educational role, inspires future professionals, and reflects society’s evolving relationship with technology. In Estonia, this relationship is particularly visible: cultural channels are increasingly used to promote cybersecurity awareness, reflecting a broader societal commitment to integrating technological development with reflective public discourse. The aim of this article is therefore to examine how popular culture can contribute to increasing citizens’ cybersecurity awareness. In doing so, it extends existing cybersecurity discourse by situating digital safety within broader cultural practices, and arguing that pop culture can fill important gaps left by conventional awareness strategies.